Evolution of Holocene Eolian Landscapes in the Glacial Lake Hind Basin, Manitoba - Wallace, Woody (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractStratigraphic investigations into dune fields in Glacial Lake Hind basin reveal three lithologic units: a lake basin unit, a lower eolian unit, and an upper eolian unit. The lake basin unit contains gleyed silty clays representing a low energy lake environment, and coarse sands and black shale gravels representing higher energy depositional environments. The lower eolian unit contains sedimentary and organic laminations and no buried soils. The upper eolian unit does not have laminations, but contains multiple buried soil profiles. Preservation of organic laminations and presence of redoximorphic colouring in the lower eolian unit suggest that it has been preserved by groundwater. The upper eolian unit contains four soil profile types that appear in sequence with an interdunal profile at the bottom and a dune profile at the top. Radiocarbon ages of soils in the upper eolian unit (2350 ± 50 and 1100 ± 40 BP) indicate regional synchronicity with soil forming periods across the northeastern Great Plains. However, the morphology of a buried soil profile depended on the site’s location on the paleolandscape during development.